ChemInform Abstract: Iodobenzene Dichloride Mediated Sequential C—Cl Bond Formation: A Safe, Convenient and Efficient Method for the Direct α, α‐Dichlorination of β‐Dicarbonyl Compounds. Issue 29 (July 2015) - Duan, Xiyan; Zhou, Huiyun; Tian, Xinlei; Liu, Jianwei; Ma, Junying
Abstract Whereas the α, α‐dichlorination of β‐dicarbonyl compounds proceeds efficiently, it is not applicable to the corresponding transformation of simple ketones.